PENGARUH LOAN TO DEPOSIT RATIO , NON PERFORMING LOAN , DAN PERTUMBUHAN DANA PIHAK KETIGA, TERHADAP PROFITABILITAS PERBANKAN: Studi pada Bank Pembangunan Daerah di Indonesia Tahun 2013-2017 - Siti Endarwati; Sulastiningsih Sulastiningsih (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
Profitability is the ability of banks to earn profit through the use of owned assets. The high profitability indicates that good bank performance. This study aims to examine the effect of Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Third Party Fund Growth (DPK) toward profitability measured by Return on Assets (ROA) in Bank Pembangunan Daerah. The study took 25 Bank Pembangunan Daerah throughout Indonesia in 2013-2017. The data analysis technique in this research used multilinear regression. The result of the study showed that DPK growth has no effect on ROA. LDR has positive significant effect on ROA. Meanwhile NPL has negative significant effect on ROA.